2020
DOI: 10.25288/tjb.604842
|View full text |Cite
|
Sign up to set email alerts
|

Kestanbol Jeotermal Akışkanının Hidrokimyasının ve Çevresel Etkilerinin Belirlenmesi

Abstract: 'nde yer alan Kestanbol jeotermal alanı, Biga Yarımadası'nın plütonik yükselimleri ile komşu metamorfik kayaçlarının kontağında bulunmaktadır. Bu alan aynı zamanda Kuzey Anadolu Fayı'nın güney kolunun batıya olan uzantılarını temsil eden DKD-BGB uzanımlı sağ yanal doğrultu atımlı bir fay segmenti ile kontrol edilmekte olup, Biga Yarımadası'ndaki en yüksek sıcaklığa sahip jeotermal alanlardan biridir. Kestanbol jeotermal alanında bulunan sondajdan çıkan jeotermal akışkan tesisin ısıtılması, termal turizm ve bal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…Scales are generally observed with yellow and orange, and occasionally white color in the field. Marmara et al (2020) reported that the As, Fe and Mn concentrations of scale are higher than the mean values for the continental crust defined by Krauskopf and Bird (1995). Kestanbol geothermal waters are highly mineralized with elevated levels of As, Ba, Fe and Mn.…”
Section: Physical and Chemical Characterizationmentioning
confidence: 69%
See 3 more Smart Citations
“…Scales are generally observed with yellow and orange, and occasionally white color in the field. Marmara et al (2020) reported that the As, Fe and Mn concentrations of scale are higher than the mean values for the continental crust defined by Krauskopf and Bird (1995). Kestanbol geothermal waters are highly mineralized with elevated levels of As, Ba, Fe and Mn.…”
Section: Physical and Chemical Characterizationmentioning
confidence: 69%
“…The geothermal waters are heated at depth by the Kestanbol Pluton and high geothermal gradient. Marmara et al (2020) identified the NE-SW trending right-lateral strike-slip Kaplica fault parallel to Ilica stream in the Kestanbol geothermal field. The fault begins at the contact between metamorphics and granites in the east and probably ends by continuing under the Aegean Sea in the west, reaching a length of nearly 10 km.…”
Section: Geological Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…Geothermal fluids of Turkey are highly mineralized with elevated levels of As, B, Cd, and Pb [13]. The high element content of geothermal fluid has certain detrimental environmental consequences, such as pollution of surface water, groundwater, and soil [14]. Tuzla geothermal field located in northwestern Turkey, approximately 70 km southwest of the Çanakkale city.…”
Section: Introductionmentioning
confidence: 99%